IMPROVING THE ELEVENTH GRADE STUDENTS’ SPEAKING ACHIEVEMENT THROUGH WHOLE BRAIN TEACHING METHOD AT SMK FARMASI BINA MEDIKA PALEMBANG - dini aulia dwintan (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
The objectives of this study were to find out: (1) whether or not there was a significant improvement in speaking achievement between before and after the students were taught by using Whole Brain Teaching method, and (2) whether or not there was a significant difference on speaking achievement between the students who were taught by Whole Brain Teaching method and those who were not. The sample of this study was 58 eleventh grade students of SMK Farmasi Bina Medika Palembang, which were divided into control and experimental groups, and each group has 29 students. The technique of selecting the sample was convenience sampling. To collect the data, each group was given a pretest and a post test. The data analyses used paired sample and independent sample t-test. The results of this study showed that (1) that the p-output (Sig. 2 tailed) was 0.000 and t-obtained was 14.376 at the significance level at 0.05 in two tailed testing with df=28. It means that there was significant improvement in students’ speaking achievement after the students were taught by using Whole Brain Teaching method, and (2) the t-obtained was 3.387 and p-output was 0.01 at the significance level 0.05 in two tailed testing with df=56. It means that there was significant difference in students’ speaking achievement between who were taught by using Whole Brain Teaching method and those who were. In conclusion, teaching speaking through Whole Brain Teaching can improve students’ speaking achievement.